Hepatitis E virus-associated Guillain-Barré syndrome: A case report (Indian Journal of Case Reports, 2026)
Guillain-Barré syndrome (GBS) is an acute immune-mediated neuropathy often triggered by infections. Hepatitis E virus (HEV), a common cause of viral hepatitis, has been increasingly linked to extrahepatic manifestations, including neurological syndromes. We report a 31-year-old man who developed progressive limb weakness and respiratory difficulty following acute diarrheal illness. Neurological examination revealed quadriparesis with reduced reflexes; nerve conduction studies showed axonal and demyelinating motor neuropathy. Cerebrospinal fluid analysis demonstrated lymphocytic pleocytosis, and HEV-immunoglobulin M was positive with concurrent hepatic dysfunction. The patient was treated with intravenous immunoglobulin and supportive care, showing gradual recovery. This case highlights HEV-associated GBS as a rare but important diagnostic consideration, particularly in endemic regions. Early recognition of HEV as a trigger in GBS can guide timely management and improve outcomes, underscoring the need for heightened clinical awareness of its extrahepatic complications.